Zmiany w mechanizmach cenotwórczych na europejskim rynku gazu ziemnego - Tarnawski, Marcin (Polityka i Społeczeństwo, 2020)
The pricing mechanism on the European gas market is an interesting issue, mainly due to the changes on the international gas markets. Although the appearance on the market of LNG is the most significant factor affecting the raw material price, we cannot forget about the others: indexation to oil prices, long-term contracts, dominance of Russian gas in the eastern part of the continent, development of infrastructure (interconnectors), and gas storage. Although natural gas does not constitute the single most important source of energy, its role and importance for certain sectors of the economy, consumers (heating) and energy sector is very important. The presentation of the changes in the mechanism of gas pricing in Europe is the main objective of the article. Factors influencing these changes (inter alia the LNG policy of Gazprom) are presented in the second part of the study. While the first part will be limited to indicating the most important elements of the price formation mechanism in long-term contracts and hubs on the European market.